Study of surface ozone at Port Blair, India, a remote marine station in the Bay of Bengal. (July 2015) - Mandal, T.K.; Peshin, S.K.; Sharma, C.; Gupta, Prabhat Kumar; Raj, Rachit; Sharma, S.K.
Abstract: This paper presents seasonal variation of surface ozone monitored continuously at site of the meteorological observatory at Port Blair, a maritime site of the Bay of Bengal for the period of August, 2005–March, 2007. Present observation depicts the characteristics of surface ozone at the remote marine site and the long range transport of pollutants from three different sides i.e., Indian Subcontinent, South East Asia and Indian Ocean. Very high ozone mixing ratio (~70–80 ppbv) is occasionally observed during March and November at this site. A campaign mode of observation of trace gases (surface ozone, CO, NO x, CO2 ), aerosol concentration and its size, UV radiation at Port Blair was made to understand the role of transport on pollutants during March 16–26, 2002. During this period of observation, a near zero surface ozone of different time scales (~few hours) has been observed several times during the period of midnight to early morning. Simultaneously NO x (NO+NO2 ) (~40 ppbv) and carbon monoxide was observed very high (300–600 ppbv) during this period. Source of this high pollutant are not expected at this remote marine sites although wind patterns, 7-days isentropic back Trajectory analysis and MATCH Model output suggest that polluted air mass has come from eastern side of Indian subcontinent. Highlights: Firsttime reporting long term surface ozone at Port Blair, a marine site in the Bay of Bengal. It suggests role of the transport of pollutants to variation of surface ozone at Port Blair particularly from east Asia. It report events of titration of ozone due to presence of large NO x in a case study of 2002.